Digital Transformation’s Effect on Supply Chain Management - Reddy, Patlolla Sathvika; Ashritha, Pilly (International Journal of Advances in Business and Management Research (IJABMR), 2023)
Supply chain management has seen substantial changes as a result of the digital transformation, which has an impact on its adaptability and resilience. The dual effects of digital transformation are explored in this abstract, which shows how businesses have leveraged technology to improve their supply chains’ resilience to disturbances and their agility to adapt to shifting consumer expectations. In order to ensure that supply chains stay resilient and flexible in a changing business climate, the study examines strategies, tools, and best practices that have helped businesses achieve this balance. Empirical research is used in this investigation.